A Case Study on Content Based Instruction for Primary School Children - Helda Alicia Hidalgo Dávila; Magda Lucy Caicedo Vela (Asociación Colombiana de Profesores de Ingles, 2011)
Teaching English at the primary school level is a challenge in countries such as Colombia where children study this language for only one hour a week in most institutions, and in the best of cases for 3 hours a week. Most of the public schools do not have enough and/or adequate English materials at their disposal for students to work with; therefore, the task of the English teacher is difficult. A case study with a group of children in public schools was developed at Universidad de Nariño (Pasto, Colombia) to test some materials developed by a group of professors who considered CBI (Content-Based Instruction) materials as an option to motivate children to learn English and as a tool for language acquisition through the subject matter contents.